Physiological and immunological changes in the brain associated with lethal eastern equine encephalitis virus in macaques. - Joseph R Albe (PLoS Pathogens, 2021)
Aerosol exposure to eastern equine encephalitis virus (EEEV) can trigger a lethal viral encephalitis in cynomolgus macaques which resembles severe human disease. Biomarkers indicative of central nervous system (CNS) infection by the virus and lethal outcome of disease would be useful in evaluating potential medical countermeasures, especially for therapeutic compounds. To meet requirements of the Animal Rule, a better understanding of the pathophysiology of EEEV-mediated disease in cynomolgus macaques is needed. In this study, macaques given a lethal dose of clone-derived EEEV strain V105 developed a fever between 2-3 days post infection (dpi) and succumbed to the disease by 6 dpi. At the peak of the febrile phase, there was a significant increase in the delta electroencephalography (EEG) power band associated with deep sleep as well as a sharp rise in intracranial pressure (ICP). Viremia peaked early after infection and was largely absent by the onset of fever. Granulocytosis and elevated plasma levels of IP-10 were found early after infection. At necropsy, there was a one hundred- to one thousand-fold increase in expression of traumatic brain injury genes (LIF, MMP-9) as well as inflammatory cytokines and chemokines (IFN-γ, IP-10, MCP-1, IL-8, IL-6) in the brain tissues. Phenotypic analysis of leukocytes entering the brain identified cells as primarily lymphoid (T, B, NK cells) with lower levels of infiltrating macrophages and activated microglia. Massive amounts of infectious virus were found in the brains of lethally-infected macaques. While no infectious virus was found in surviving macaques, quantitative PCR did find evidence of viral genomes in the brains of several survivors. These data are consistent with an overwhelming viral infection in the CNS coupled with a tremendous inflammatory response to the infection that may contribute to the disease outcome. Physiological monitoring of EEG and ICP represent novel methods for assessing efficacy of vaccines or therapeutics in the cynomolgus macaque model of EEEV encephalitis.